Study of the relationship between "attitude towards the usefulness of mathematics" and "mathematical self-confidence" in two Costa Rican high schools: Estudio de la relación entre la "actitud hacia la utilidad de la matemática" y la "autoconfianza matemática" en dos colegios costarricenses - Sequeira Solano, Robin (2025)
The affective component plays a significant role in the teaching and learning process of mathematics. This study investigates the relationship between the attitude toward the usefulness of mathematics and mathematical self-confidence in a sample of 476 students from a rural and an urban school, both public and daytime, in Costa Rica. The variables were measured using the Fennema and Sherman subscales. The results indicate that both variables exhibit high levels, with 87.4% of the students showing a positive attitude toward the usefulness of mathematics and 65.8% displaying high mathematical self-confidence. Significant differences were identified in mathematical self-confidence based on sex, although no differences were observed in the attitude toward the usefulness of mathematics. Similarly, variations were found in both variables depending on the type of school, with the rural school showing the highest averages. No significant differences were found in any of the variables based on educational level. Finally, a positive, weak, and linear relationship was detected between the attitude toward the usefulness of mathematics and mathematical self-confidence.